Rome's most faithful daughter: the Catholic Church and independent Poland, 1914-1939 - Pease, Neal (Ohio University Press Polish and Polish-American studies series, 2009)
When an independent Poland reappeared on the map of Europe after World War I, it was widely regarded as the most Catholic country on the continent, as "Rome's Most Faithful Daughter." All the same, the relations of the Second Polish Republic with the Church-both its representatives inside the country and the Holy See itself-proved far more difficult than expected. Rome's Most Faithful Daughter: The Catholic Church and Independent Poland, 1914-1939 presents the first scholarly history of the close but complex political relationship of Poland with the Catholic Church during the interwar period. Neal Pease addresses the centrality of Poland in the Vatican's plans to convert the Soviet Union to Catholicism and the curious reluctance of each successive Polish government to play the role assigned to it. He also reveals the complicated story of the relations of Polish Catholicism with Jews, Freemasons, and other minorities within the country and what the response of Pope Pius XII to the Nazi German invasion of Poland in 1939 can tell us about his controversial policies during World War II. --From publisher's description